IMPLEMENTASI LOGIKA FUZZY DALAM MENENTUKAN JURUSAN SISWA BARU: (STUDI KASUS : SMK TAMAN SISWA RANCAEKEK) - Siti Yuliyanti; Wulan Suryani; Haris Irnawan (LPPM STMIK BANDUNG, 2020)
Education plays a very important role in the process of improving the quality of human resources. The process of selecting a course for prospective students by SMK Taman Siswa Rancaekek is done in a way that is still manual. The research aims to analyse new students in determining the majors that match their talents, interests and abilities. Therefore, the results of this research built the Fuzzy logic implementation system using Tsukamoto method, from the research results get that Tsukamoto method is able to provide recommendations according to subjects that have value High.